Realism and Dramatic Art (Study in Harmony Realistic Theories with Theater Elements) (Journal of Hama University, 2019)
This research strives to reveal the harmony between the realism of literature as a literary school and the elements of dramatic art as a literary genre, while studying the elements of theatrical art in the face of the school's realism.The search for this is based on the views of the theoreticians of realism and their critics who preferred the novel to other literary genres as the ideal genre that meets the principles and characteristics of realism.The study then examines the Features of realism in the elements of dramatic art beginning with the nature of the theater, which is defined as the simulation of an act, and the extent to which this is related to reality.The study examines the subject of mimesis in the theater, and examines the plot, personality and thought, indicating the connection of these concepts with the characteristics of realism and its statements such as objectivity and modeling of characters and intellectual system.The study examines the mimesis material in the theater, which is its language and nature of dialogue, and shows the extent to which relates to the realism in ease and the use of socially known language.The research examines the goal of the theater and its social message, and shows the compatibility of this with the message of realist social literature.Finally, the research shows the compatibility between realism and theater for their participation in the sociological aspect.The research concludes that the theater is closely related to the school and its realism. Dramatic art is capable of carrying out the real characteristics of the school, fulfilling its